Teaching and Learning Responsibilities: An analysis of workload and resultant stress on productivity and effectiveness in middle leaders. - Bosano, Melissa (2018)
There exists a significant amount of research exploring teacher resilience and teacher stress as a result of workload. Research has also been carried out into the importance of the role of middle managers in schools. Workload and resultant stress in middle management merit further exploration however, and so the focus of this research is to bridge the gap between these two areas and explore how middle managers are affected by workload, and how this can affect their own efficacy as teachers and leaders. This study hopes to find ways to protect the valued role played by middle managers in schools and find ways of improving their workload/efficiency balance. This dissertation adopts two separate research approaches. The first explores the existing relevant literature and the second involves empirical research. The latter was carried out via a questionnaire administered to middle managers across 3 school sectors in the local area. The findings from this research provide evidence that middle leaders in Gibraltarian schools feel that their workload is negatively affecting their levels of stress and preventing full efficacy in their post. The main conclusions drawn from this study are that the workload of middle leaders is indeed rising, however this has not been accompanied by an increase in the time allocated to middle leaders to allow them to complete all requisite tasks and duties effectively. This dissertation recommends that these issues be explored further in order to safeguard the role of the middle manager and provide an equitable balance between workload and efficacy.